Step
*
1
1
2
1
of Lemma
increasing-sequence-converges
1. x : ℕ ⟶ ℝ
2. ∀n:ℕ. ((x n) < (x (n + 1)))
3. c : {2...}
4. m : ℕ+
5. ∀n:ℕ+. (((x (n + 1)) - x n) ≤ ((r1/r(c)) * ((x n) - x (n - 1))))
6. (r(c) * ((x 1) - x 0)/r(c - 1)) ≤ (r1/r(m))
7. n : ℤ
8. 0 < n
9. ((x (n + 1)) - x n) ≤ ((r1/r(c^n)) * ((x 1) - x 0))
10. ((x ((n + 1) + 1)) - x (n + 1)) ≤ ((r1/r(c)) * ((x (n + 1)) - x ((n + 1) - 1)))
⊢ ((r1/r(c)) * ((x (n + 1)) - x ((n + 1) - 1))) ≤ ((r1/r(c^n + 1)) * ((x 1) - x 0))
BY
{ ((Subst' (n + 1) - 1 ~ n 0 THENA Auto)
   THEN MoveToConcl (-2)
   THEN GenConclTerms Auto [⌜(x (n + 1)) - x n⌝;⌜(x 1) - x 0⌝]⋅) }
1
1. x : ℕ ⟶ ℝ
2. ∀n:ℕ. ((x n) < (x (n + 1)))
3. c : {2...}
4. m : ℕ+
5. ∀n:ℕ+. (((x (n + 1)) - x n) ≤ ((r1/r(c)) * ((x n) - x (n - 1))))
6. (r(c) * ((x 1) - x 0)/r(c - 1)) ≤ (r1/r(m))
7. n : ℤ
8. 0 < n
9. ((x ((n + 1) + 1)) - x (n + 1)) ≤ ((r1/r(c)) * ((x (n + 1)) - x ((n + 1) - 1)))
10. v : ℝ
11. ((x (n + 1)) - x n) = v ∈ ℝ
12. v1 : ℝ
13. ((x 1) - x 0) = v1 ∈ ℝ
⊢ (v ≤ ((r1/r(c^n)) * v1)) 
⇒ (((r1/r(c)) * v) ≤ ((r1/r(c^n + 1)) * v1))
Latex:
Latex:
1.  x  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}
2.  \mforall{}n:\mBbbN{}.  ((x  n)  <  (x  (n  +  1)))
3.  c  :  \{2...\}
4.  m  :  \mBbbN{}\msupplus{}
5.  \mforall{}n:\mBbbN{}\msupplus{}.  (((x  (n  +  1))  -  x  n)  \mleq{}  ((r1/r(c))  *  ((x  n)  -  x  (n  -  1))))
6.  (r(c)  *  ((x  1)  -  x  0)/r(c  -  1))  \mleq{}  (r1/r(m))
7.  n  :  \mBbbZ{}
8.  0  <  n
9.  ((x  (n  +  1))  -  x  n)  \mleq{}  ((r1/r(c\^{}n))  *  ((x  1)  -  x  0))
10.  ((x  ((n  +  1)  +  1))  -  x  (n  +  1))  \mleq{}  ((r1/r(c))  *  ((x  (n  +  1))  -  x  ((n  +  1)  -  1)))
\mvdash{}  ((r1/r(c))  *  ((x  (n  +  1))  -  x  ((n  +  1)  -  1)))  \mleq{}  ((r1/r(c\^{}n  +  1))  *  ((x  1)  -  x  0))
By
Latex:
((Subst'  (n  +  1)  -  1  \msim{}  n  0  THENA  Auto)
  THEN  MoveToConcl  (-2)
  THEN  GenConclTerms  Auto  [\mkleeneopen{}(x  (n  +  1))  -  x  n\mkleeneclose{};\mkleeneopen{}(x  1)  -  x  0\mkleeneclose{}]\mcdot{})
Home
Index